Curcumin and Vitamin E Protect against Adverse Effects of Benzo[a]pyrene in Lung Epithelial Cells - Zhu, Wenbin; Cromie, Meghan M.; Cai, Qingsong; Lv, Tangfeng; Singh, Kamaleshwar; Gao, Weimin (PLOS ONE, 2014)
Benzo[a]pyrene (BaP), a well-known environmental carcinogen, promotes oxidative stress and DNA damage. Curcumin and vitamin E (VE) have potent antioxidative activity that protects cells from oxidative stress and cellular damage. The objectives of the present study were to investigate the adverse effects of BaP on normal human lung epithelial cells (BEAS-2B), the potential protective effects of curcumin and VE against BaP-induced cellular damage, and the molecular mechanisms of action. MTT assay, flow cytometry, fluorescence microplate assay, HPLC, qRT-PCR, and western blot were performed to analyze cytotoxicity, cell cycle, reactive oxygen species (ROS), BaP diol-epoxidation (BPDE)-DNA adducts, gene expression, and protein expression, respectively. Curcumin or VE prevented cells from BaP-induced cell cycle arrest and growth inhibition, significantly suppressed BaP-induced ROS levels, and decreased BPDE-DNA adducts. While CYP1A1 and 1B1 were induced by BaP, these inductions were not significantly reduced by curcumin or VE. Moreover, the level of activated p53 and PARP-1 were significantly induced by BaP, whereas this induction was markedly reduced after curcumin and VE co-treatment. Survivin was significantly down-regulated by BaP, and curcumin significantly restored survivin expression in BaP-exposed cells. The ratio of Bax/Bcl-2 was also significantly increased in cells exposed to BaP and this increase was reversed by VE co-treatment. Taken together, BaP-induced cytotoxicity occurs through DNA damage, cell cycle arrest, ROS production, modulation of metabolizing enzymes, and the expression/activation of p53, PARP-1, survivin, and Bax/Bcl-2. Curcumin and VE could reverse some of these BaP-mediated alterations and therefore be effective natural compounds against the adverse effects of BaP in lung cells.